Aladdin (Disney Movie Collection: A Special Disney Storybook Series, 2015)
When Aladdin steals a magic lamp, he becomes the master of the genie inside who can grant Aladdin three wishes. But the sultan's evil advisor, Jafar, will stop at nothing to get the lamp for himself. With the Genie's help, can Aladdin defeat Jafar, save the kingdom and win the heart of Princess Jasmine?Enjoy this exclusive large size Disney movie storybook, featuring beautifully illustrated pages fans can treasure for years to come.